Therapeutic plasmapheresis: an eleven-year clinical experience - Tekdöş Şeker, Yasemin; Hergünsel, Gülsüm Oya; Özel Bilgi, Deniz (The European Research Journal, 2018)
Objective: Therapeutic plasma exchange (TPE) is currently indicated as an alternative treatment regimen in a number of guidelines for various medical conditions. In this article we retrospectively reviewed cases who underwent TPE in Bakırköy Dr. Sadi Konuk Training and Research Hospital intensive care unit between 2007 and 2016 and compared the findings to the current reports in the literature. Methods: A total of 80 cases were treated with TPE between 2007 and 2016 in our intensive care unit. Information on demographic variables, therapeutic indications, catheterized veins, complications during the procedure, number of sessions, replacement products used and survival data was collected. In addition, pre- and post-procedure serum triglyceride, cholesterol and amylase levels were also collected in acute pancreatitis cases associated with hypertriglyceridemia. Results: A total of 501 TPE sessions were performed on 80 cases comprising 35 neurology, 18 hematology, 12 hypertriglycemic acute pancreatitis and 7 acute hepatic insufficiency patients, along with 8 cases with less common indications including sepsis, hyperthyroidism resistant to medical therapy and toxic epidermal necrolysis. The age of the subjects ranged between 12 and 82 years (mean; 45.08 ± 14.67 years). Sixteen (23.19%) cases died before the completion of the planned sessions. Pre- and post-procedure serum triglyceride, cholesterol and amylase levels were significantly different in acute pancreatitis cases (p < 0.05). Conclusion: Timely implementation of TPE in applicable indications may be helpful in preventing morbidity and mortality in a wide spectrum of disorders.